PENGARUH EARNING PER SHARE, PRICE EARNING RATIO, DAN PRICE TO BOOK VALUE TERHADAP HARGA SAHAM PERUSAHAAN ASURANSI - Wala, Salsa Hashinah; Megawati, Liya; Wahidin, Wahidin (LPPM Universitas Bina Bangsa, 2025)
Investigating the connection between earning per share, dan price-to-earnings ratio, dan price-to-book value is the goal of this study. All general insurance businesses listed on the Indonesia Stock Exchange between 2019 and 2023 make up the study's population. Multiple linear regression approaches are used as a quantitative tool in this investigation. Purposive sampling is used in the research sample. Multiple linear regression, classical assumptions, descriptive and verificative analysis, and hypothesis testing are some of the statistical techniques used in this study. This study shows that a variety of factors affect the stock values of general insurance businesses. Earning per share, dan price-to-earnings ratio, dan price-to-book value are the variables. When taken as a whole, these three factors have a consistent impact on stock prices